(untitled) (Journal of Electrical, Electronics and Informatics, 2026)
The government of Bali Province has announced to achieve Net Zero Emission (NZE) target by 2045; therefore, energy transition strategy currently becomes a challenge for the government. An accelerated implementation of renewable energy (RE) power generation was introduced as part of the strategy. This study is focused on the investigation of energy mix optimization for power generation using the Low Emission Analysis Platform (LEAP) software. The analysis was carried out for a period of year 2025 to 2045. Three scenarios were introduced for the analysis, namely optimistic, moderate, and pessimistic. The three scenarios were differentiated based on energy policies, technology penetration levels, and decarbonization targets at national and regional levels. The model was validated using actual energy consumption data and then simulated to project electricity demand and power generation mixture. The analysis results show that with the optimistic scenario, the proportion of RE supply could reach 51.1% in 2045, dominated by solar PV and geothermal power, following the complete phase-out of coal-fired and diesel power plants. The moderate scenario introduces an RE proportion of 19.3%, with a slightly slower transition acceleration. The pessimistic scenario however; indicated that the fossil fuel power plant may be still in use until the end of year 2045, with RE contribution of about 7.4%, reflecting a condition without accelerated energy transition. The analysis results thus conclude that to achieve Bali NZE in 2045, it is necessary to implement a strategy that accelerating the RE investment, strengthening supportive policies, and gradual phase-out of fossil-fuel power plants.